EFFECTIVENESS OF SUCTION ABOVE CUFF ENDOTRACHEAL TUBE (SACETT) IN PREVENTING VENTILATOR ASSOCIATED PNEUMONIA IN CRITICAL PATIENTS IN INTENSIVE CARE UNIT - Arfiyan Sukmadi; Rr Sri Endang Pujiastuti; Aris Santjaka; Supriyadi Supriyadi (Belitung Nursing Journal, 2018)
Background: The mechanical ventilator is an indispensable breathing tool in the Intensive Care Unit (ICU). But the mechanical ventilator is associated with the risk of Ventilator Associated Pneumonia (VAP). VAP occurs due to poor hygiene of the endotracheal tube (ETT). ETT hygiene should be maintained to inhibit bacterial development in the lungs using suction above cuff endotracheal tube (SACETT) to prevent VAP. Objective: To analyze the effectiveness of SACETT in preventing Ventilator Associated Pneumonia (VAP) in critical patients in the ICU. Methods: This was a quasi-experimental study with posttest only with control group design with 15 samples in intervention group (SACETT and Chlorhexidine 0.2%) and 15 in control group (ETT, Open Suction, and Chlorhexidine 0.2%) with purposive technique sampling. The Simplified Clinical Pulmonary Infection Score (CPIS) was used to measure VAP. Results: This study illustrates that there was no VAP incidence in the intervention group, and as much as 13.3% VAP in the control group. SACETT was more effective in preventing VAP than in standard ETT on day 4 (p = 0.001). Conclusion: SACETT is more effective in preventing VAP than standard ETT in the fourth day in patients with neurological, cardiovascular, urinary, digestive, and immune system disorders.